Multiple spawning and length of embryonic development of Munida gregaria in northern Patagonia (Argentina) - Dellatorre, Fernando Gaspar (2008)
Munida gregaria is a small galatheid widely distributed around the southern hemisphere, considered a key species in food webs of coastal and shelf marine ecosystems. Previous studies conducted at 55°S and 46°S on the Atlantic coast of South America, have shown that the species can adapt its reproductive patterns to different environmental conditions. The objectives of this work are to complete this analysis by determining: (1) the reproductive season span; (2) the potential of the species to produce multiple clutches of eggs; (3) the length of its embryonic development; and (4) based on previous objectives, the potential number of clutches produced by M. gregaria by reproductive season in the northern range of its coastal distribution (42-43°S, northern Patagonia). In this region, brooding females were present from June to December, representing more than 80% of total females between July and October. Females presented previtellogenic oocytes beginning maturation just after egg extrusion, and fully developed vitellogenic oocytes just before hatching. From November to February increasing proportions of females showed signs of athresia and resorption of mature oocytes. The complete embryonic development of M. gregaria lasted 26-29 days at 11°C constant temperature. Considering the pattern of synchronous ovary re-maturation and embryonic development, the length of embryogenesis at water temperatures typical from costal waters off northern Patagonia during the breeding season, it is concluded that female M. gregaria have the potential to consecutively lay more than three egg clutches per reproductive season. Copyright © Marine Biological Association of the United Kingdom 2008.